Profile, motivations and the challenges of artistc gymnastics coaches in Brazil - Nunomura, M.; Santos Oliveira, M. (High performance gymnastics, 2014)
As most of the Brazilian AG coaches have a degree in physical education, we suppose that all of them acquired the necessary knowledge that support their coaching and competencies to initiate gymnasts in their first steps in this sport. It would be important and advisable that coaches seek for AG courses that will complement the knowledge they got at university, mostly, due to the limited time and few subjects in gymnastics offered at physical education courses. Other important aspect is related to the new methods and knowledge that are developed over the years. Therefore, updating is essential to improve him/herself as a coach. However, we come to the following questions: Are there AG specialization courses or enough scientific groundings offered in higher education? Are there meetings nurturing the exchange of experiences among the professionals in Brazil? The authors agree with Nunomura (2001), who proposes the creation of a Gymnastics Association in Brazil, in which the dialogue among the several institutions that are involved with this sport would be possible, especially universities, federations, and sports centers, aiming to promote the education, qualification and updating of professionals involved in AG. Another important initiative involves scientific events, such as SIGARC (International Seminar of Competitive Artistic and Rhythmic Gymnastics). It has a great value in the coaches' education, due to the knowledge presented and discussed, especially, those related to the high level of sport. Moreover, this kind of event makes possible to coaches to join other professionals and academics, and share experiences. During the study we realized that many coaches did not have a previous experience with this sport as a gymnast. There is hope that this aspect will stimulate those professionals who feel apprehensive with the supposed disadvantage regarding the former gymnasts to get involved with the sport. An additional highlighted role that the university could play in the AG specialized education, would be to offer opportunities for the undergraduate students to experience the teaching and learning process of AG in the extension programs at the university, which allows the practice of coaching in an actual learning process. The study also points out that the gymnastics lecturer at the higher education can be one of the greatest motivators for the coming coaches. Then, it is essential that the faculty members are conscious of their disseminating and encouraging role in this sport. Regarding coaches' work conditions, the study revealed that despite many of them do not have benefited from the satisfactory conditions of work (i.e. physical infrastructure, FIG approved apparatus, human resources and institutional support), it was still possible to observe outstanding results. The logic that explains the fact relies on devoted coaches and athletes who invest in their on careers. This situation allow them to keep the quality of their work and results, added to the support of local government and few sport clubs in Brazil. This reality reveals that Brazil has a potential to stand out even more in the international sporting scenario, as there are both talented coaches and athletes. However, the efforts and investments should be shared among all those who are involved in the development of this sport in the country.